LEGAL PROTECTION FOR DOCTORS IN LEGAL DISPUTES IN HOSPITALS FROM THE PERSPECTIVE OF EMPLOYMENT AGREEMENTS - Wijaya, Deni (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
This research aims to analyze the form of legal protection provided to doctors in cases of legal disputes in hospitals, especially in the context of work agreements. The method used in this research is a qualitative method, which allows researchers to explore and understand the phenomena that occur in more depth. Data was collected through in-depth interviews, document studies and participant observation. The research results show that legal protection for doctors is greatly influenced by the provisions in the employment agreement between the doctor and the hospital. The conclusion of this research is the need to strengthen legal aspects in employment agreements to ensure doctors receive adequate protection in facing legal disputes.